Increased leptin storage with altered leptin secretion from adipocytes of rats with sucrose-induced dyslipidemia and insulin resistance: effect of dietary fish oil - Selenscig, Dante Alejandro (2010)
This study examined the effect of long-term feeding a high-sucrose diet (SRD) on the modulation of rat adipocyte's leptin secretion and storage. For this purpose, we analyzed (a) basal and insulin-stimulated leptin release and the role of isoproterenol and palmitate on insulin-stimulated leptin secretion, (b) the correlation between leptin and glycerol released, (c) the relationship between leptin contents and adiposity, and (d) the effect of fish oil (FO) administration on the above parameters. Wistar rats were fed an SRD for 6 months. Whereas half the animals continued with SRD up to month 8, the other half was fed an SRD in which FO partially replaced corn oil from months 6 to 8. Total leptin release was reduced both basally and under insulin stimulation in SRD-fed rats. However, the ratio of leptin released after hormone stimulation to basal leptin levels was similar in the 3 dietary groups. Isoproterenol inhibited insulin-stimulated leptin release in the 3 groups, but the percentage was lower in the SRD. Palmitic acid mimicked the effect of isoproterenol. Leptin release from adipocyte of SRD-fed rats negatively correlated with glycerol release. Leptin store increased in fat pads of SRD and positively correlated with adiposity. Fish oil reduced leptin content and fat pad hypertrophy, and normalized basal lipolysis, leptinemia, and glucose homeostasis. This suggests that enhanced lipolysis and altered insulin sensitivity could play a role in the decrease of leptin released in SRD-fed rats. This is consistent with the reversion of all the alterations after FO administration.